2013
DOI: 10.1097/wnf.0b013e318288076a
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Outcome in Cerebrotendinous Xanthomatosis Treated With Chenodeoxycholic Acid

Abstract: Beginning CDCA treatment as early as possible is crucial to preventing neurological damage and deterioration in CTX. After significant neurological pathology is established, the effect of treatment is limited and deterioration may continue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 16 publications
(6 reference statements)
2
82
1
2
Order By: Relevance
“…The beneficial effects of CDCA treatment on neurologic manifestations are generally greater when treatment is started earlier in the disease course (Yahalom et al 2013), suggesting that damage due to deposition of cholesterol and cholestanol in nerve tissues may be reversible and related clinical Fig. 3 Fluid-attenuated inversion recovery (FLAIR) images in transverse orientation showing a bilateral hyperintensity of the dentate nuclei and the surrounding cerebellar white matter.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The beneficial effects of CDCA treatment on neurologic manifestations are generally greater when treatment is started earlier in the disease course (Yahalom et al 2013), suggesting that damage due to deposition of cholesterol and cholestanol in nerve tissues may be reversible and related clinical Fig. 3 Fluid-attenuated inversion recovery (FLAIR) images in transverse orientation showing a bilateral hyperintensity of the dentate nuclei and the surrounding cerebellar white matter.…”
Section: Treatmentmentioning
confidence: 99%
“…The safety of CDCA in pregnant patients has not been extensively studied or reported. Published data include reports of five patients with CTX who became pregnant and gave birth to healthy babies while on CDCA (Moghadasian et al 2002;Yahalom et al 2013); while abstaining from CDCA treatment, some of these patients experienced difficulties conceiving, miscarriages, and stillbirths at term (Yahalom et al 2013). These difficulties with pregnancy in patients with untreated CTX are consistent with reports of fetal and/or infant deaths in families with CTX and premature births and mental retardation in children born to mothers with CTX (Clayton et al 2002;Berginer et al 1988), suggesting that pregnancy in untreated CTX may be a high-risk condition.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have reported clinical efficacy of CDCA in CTX including lengthy longitudinal studies after initiation of therapy. Importance of early initiation of therapy was emphasized by a recent report of 18 patients with up to 23 years on CDCA therapy in which there was a correlation between early age at initiation of CDCA therapy and improved neurological outcomes (Yahalom et al 2013). There are fewer reports of outcomes during childhood with CDCA treatment of those that become symptomatic at an early age.…”
Section: Discussionmentioning
confidence: 99%
“…The development of symptoms and signs can be halted or prevented by supplementation of CDCA, which downregulates both bile acid and cholesterol synthesis through a feedback mechanism that results in the inhibition of cholesterol-7-hydroxylase and HMG-CoA reductase, respectively, thereby preventing the production and accumulation of cholesterol and cholestanol (5). The prognosis of CTX is good when therapy is started early but is less favorable when initiated at a later age (6)(7)(8)(9). An early start to the therapy can prevent the neurological phenotype completely, and patients are expected to remain symptom-free if treatment is started immediately after neonatal diagnosis (7,10).…”
mentioning
confidence: 99%